Investigating Vocal Emotion Perception Using Auditory Emotion Recognition Task in Hindi-Speaking Children With Cochlear Implants: A Pilot Study. - Saluja, Nityansh; Chaudhary, Anchal; Verma, Himanshu; Mishra, Roshani; Nagamani, Banumathy; Pandad, Naresh K. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: This study investigates vocal emotion perception in Hindi-speaking children with cochlear implants (CIs) and children with normal hearing (NH) using auditory emotion recognition tasks. Whereas previous research has largely focused on accuracy, this study evaluates both accuracy and reaction time (RT), offering a behavioral measure of processing efficiency in recognizing five vocal emotions: happy, sad, angry, fear, and surprise. Method: Twenty children aged 4-12 years participated in the study: 10 with CIs and 10 with NH, matched for hearing age and gender. Fifty emotionally intoned Hindi sentences were validated and presented auditorily, followed by two emotion-specific animated images. Participants selected the image matching the heard emotion, and their accuracy and RTs were recorded using DMDX software. Statistical analyses included two-way analyses of variance (ANOVAs) for normally distributed emotions (sad, angry, and surprise) and Kruskal--Wallis tests for nonnormally distributed emotions (happy, fear), with Bonferroni-corrected post hoc comparisons. Results: Children with CIs showed significantly lower accuracy and longer RTs compared to children with NH. A two-way ANOVA revealed a significant main effect of group on accuracy, F(1, 54) = 6.20, p = .013, η² = .06; post hoc analysis indicated significantly lower accuracy for the angry emotion in CI users (p = .006). RT analysis also revealed a robust main effect of group, F(1, 54) = 22.71, p < .001, η² = .30, indicating slower responses in the CI group (mean RT = 5.57 s ± 0.18) than in the NH group (mean RT = 3.62 s ± 0.18). For normally distributed emotions, between-group differences were significant for sad, angry, and surprise (p < .001). For nonnormally distributed emotions, between-group differences were also significant for happy (p = .006) and fear (p < .001). Thus, all five emotions showed significantly longer RTs in the CI group. Conclusions: Hindi-speaking children with CIs demonstrated reduced speed and accuracy in identifying vocal emotions, indicating challenges in processing emotional prosody. These findings highlight the need for integrating explicit training in emotional prosody within auditory rehabilitation programs for pediatric CI users to improve social communication outcomes.